THE ROLE OF INSTITUTIONAL OWNERSHIP MODERATING CAPITAL STRUCTURE, PROFITABILITY, AND MANAGERIAL OWNERSHIP ON COMPANY VALUES - Taufiq Hidayat; Puji Endah Purnamasari (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2023)
The proportion of the value of capital structure, profitability, managerial ownership, and institutional ownership greatly influences the company's performance in increasing the value of the company so that it has an impact on shareholder wealth. This research aims to determine and analyze the relationship between capital structure, profitability, and managerial ownership of company value with institutional ownership asianmoderating variable. The research uses company objects in the consumer goods industry sector for 2019-2021. The research method uses quantitative research with a descriptive approach, data collection techniques using the documentation method, and data analysis techniques using multiple linear regression analysis and Moderated Regression Analysis (MRA) using the SPSS 23 application. Partially, the capital structure does not affect company value. Profitability and managerial ownership have a positive effect on the company value. The moderation test of institutional ownership cannot moderate the positive effect of capital structure and managerial ownership non-company value, and institutional ownership can moderate the negative effect of profitability on company value.